Omalizumab in IgE-Mediated Food Allergy: A Systematic Review and Meta-Analysis - Zuberbier, Torsten; Wood, Robert A; Bindslev-Jensen, Carsten; Fiocchi, Alessandro; Chinthrajah, R Sharon; Worm, Margitta; Deschildre, Antoine; Fernandez-Rivas, Montserrat; Santos, Alexandra F; Jaumont, Xavier; Tassinari, Paolo (The journal of allergy and clinical immunology in practice (Cambridge, MA), 2023)
A growing number of studies have shown encouraging results with omalizumab (OMA) as monotherapy and as an adjunct to oral immunotherapy (OMA+OIT) in patients with single/multiple food allergies. To evaluate the efficacy and safety of OMA or OMA+OIT in patients with immunoglobulin E (IgE)-mediated food allergy. An extensive literature search (inception to December 31, 2020) was performed to identify randomized, controlled, and observational studies that assessed OMA as monotherapy or OMA+OIT in patients with IgE-mediated food allergy. The outcomes were an increase in tolerated dose of foods, successful desensitization, sustained unresponsiveness, immunological biomarkers, severity of allergic reactions to food, quality of life (QoL), and safety. A P less than .05 was considered significant. In total, 36 studies were included. The OMA monotherapy (vs pre-OMA) significantly increased the tolerated dose of multiple foods; increased the threshold of tolerated dose for milk, egg, wheat, and baked milk; improved QoL; and reduced food-induced allergic reactions (all P < .01). The OMA+OIT significantly increased the tolerated dose of multiple foods (vs placebo and pre-OMA), desensitization (vs placebo+OIT and pre-OMA) (all P ≤ .01), and improved QoL (vs pre-OMA) and immunoglobulin G4 levels (both P < .01). No major safety concerns were identified. In IgE-mediated food allergy, OMA can help patients consume multiple foods and allow for food dose escalation. As an adjunct to OIT, OMA can also support high-dose desensitization and higher maintenance doses. Further studies are warranted to empirically evaluate the effect of OMA and confirm these findings.